Semitransparent Energy‐Storing Functional Photovoltaics Monolithically Integrated with Electrochromic Supercapacitors. (5th February 2020) - Cho, Junhee; Yun, Tae Yong; Noh, Hye Yeon; Baek, Seung Hun; Nam, Minwoo; Kim, Byunghoon; Moon, Hong Chul; Ko, Doo‐Hyun
Abstract: Energy‐storing functional photovoltaics, which can simultaneously harvest and store solar energy, are proposed as promising next‐generation multifunction energy systems. For the extension of conventional organic photovoltaics (OPVs), electrochromic supercapacitors (ECSs) are monolithically integrated with semitransparent (ST) quaternary blend‐based OPVs (ST Q‐OPVs) to achieve compact, energy‐efficient storage with great aesthetic appeal. In particular, ST Q‐OPVs with low‐power‐consumption ECSs allow full operation, even under low‐intensity irradiance, including artificial indoor light circumstances, and thereby exhibit potential for all‐day operating energy suppliers. The prepared ST energy‐storing functional photovoltaics also serve as a backup power source for external electronic equipment (e.g., light‐emitting diodes, and sensor nodes for Internet of Things) by consuming charged power. In addition to features that include unrestricted operation under any circumstances, color tunability, feasibility of designs with various shapes, rapid charging/discharging, and real‐time indication of stored energy levels, ST energy‐storing functional photovoltaics could potentially be applied in electronic devices such as advanced smart windows or portable smart electronics. Abstract : Semitransparent energy‐storing functional photovoltaics are developed by integrating quaternary blends‐based organic photovoltaics and electrochromic supercapacitor in a monolithic structure. Highly efficient operation under versatile irradiation circumstances including outdoor sun and ambient artificial indoor lighting and feasibility of any designed shape, size, and color can extend potentials for practical applications.